On the Practical Output h-Stabilization of Nonlinear Uncertain Systems - Damak, H. (Journal of Applied Nonlinear Dynamics, 2026)
This paper investigates the problem of output feedback h-stabilization of nonlinear uncertain systems. We construct an output feedback controller that guarantees global uniform practical h-stability of the closed-loop system. Our original results generalize well-known fundamental results: practical stability, practical asymptotic stability and practical exponential stability for nonlinear time-varying systems. Finally, two numerical examples are presented to demonstrate the validity of the proposed method.